Impacts and management strategies for crop production in waterlogged or flooded soils: A review. (13th March 2020) - Kaur, Gurpreet; Singh, Gurbir; Motavalli, Peter P.; Nelson, Kelly A.; Orlowski, John M.; Golden, Bobby R.
Abstract: Globally, flooding is one of the most damaging abiotic stresses, besides drought, that affects 17 million km 2 of land surface annually. Recent research indicates that climate change is resulting in more extreme weather events, such as flooding or soil waterlogging, that negatively affect crop production. Therefore, it is imperative to understand how flooding stress affects crops and to develop improved production practices that make cropping systems more resilient and able to cope with extreme weather events. This review paper summarizes the current state of knowledge on the impacts of flooding or soil waterlogging on crop production losses, nitrogen (N) losses, and provides potential management strategies to reduce these losses. The factors affecting the extent of flooding injury in plants as well as plant adaptations under waterlogging stress are also discussed briefly. For the purpose of this review, "flooding" refers to the situation when all or part of the plant is submerged under water, whereas "soil waterlogging" refers to the situation where soil pores are saturated with water. Soil waterlogging also promotes soil N losses through runoff, leaching, and denitrification. Potential management practices that can be used to mitigate soil waterlogging stress include the use of flood‐tolerant varieties, adjusting management practices, improving drainage, and practicing adaptive nutrient management strategies. However, these might be site‐ or crop‐specific management practices and they should be validated for their economic viability before developing future management plans that promote sustainable crop yields from waterlogged soils.